High‐Throughput Sequencing in Aquaculture Disease Investigations: Challenges and Opportunities for Implementation - Francisca Samsing; Phoebe Arbon; Matthew Arnold; Andrew C. Barnes; David Bass; Joy A. Becker; Jerusha Bennett; Charles Caraguel; Jeremy Carson; Vincenzo A. Costa; Thomas Dumond; Jemma Geoghegan; et al. (Reviews in Aquaculture, 2026)
The current generation of sequencing technologies can produce terabases of data with exceptional accuracy and speed, at a fraction of the cost of older methods. Despite this unprecedented power, adoption into aquaculture health management presents several challenges, including identifying where such capability may be optimally deployed. Here we synthesise discussions from a structured expert workshop held at the 2025 Aotearoa Aquatic Diseases Symposium in Dunedin, New Zealand, where experts from industry, government and academia explored the challenges and opportunities for adopting high‐throughput sequencing (HTS) to support disease investigations in aquaculture. Workshop participants identified key applications for HTS, including pathogen discovery during unexplained mortality events and source attribution in epidemics, but also noted technical, regulatory and social challenges for widespread adoption. These include the need for standardised sampling and bioinformatic workflows, data sovereignty, equitable access to the technology and uncertainty around interpreting detection of notifiable pathogens. Targeted research and coordinated regulatory frameworks will be essential to guide responsible use of HTS and determine where it adds value relative to existing approaches. Clarifying these opportunities and constraints will guide the responsible adoption of HTS into aquaculture health management to support sustainable growth for the sector.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

A phase I clinical study to evaluate rapid, high-volume, subcutaneous auto-injector tolerability with recombinant human hyaluronidase - David W. Kang; Robert J. Connor; Tara Nekoroski; Jo Ann M. Bitsura; Susan K. Kindig; Stephen P. Knowles; Michael J. LaBarre (Drug Delivery and Translational Research, 2026)
Until recently, approved handheld auto-injectors (AIs) have been limited to volumes ≤ 2 mL. A prototype rapid high-volume AI (HVAI) that can deliver 10 mL in 30 s was developed to administer therapeutics co-formulated with a proprietary recombinant human hyaluronidase PH20 (rHuPH20). This phase I, open-label study assessed the tolerability of subcutaneous (SC) injections of 10% (100 mg/mL) immunoglobulin G (IgG) solution co-administered with 4000 U/mL rHuPH20, delivered using a syringe pump at a target rate of 5 or 10 mL/30 seconds or the prototype HVAI at a target rate of 10 mL/30 seconds in healthy human subjects. Subjects received 5 mL (Cohort A, n = 12) or 10 mL (Cohort B, n = 12) of test solution via syringe pump (injection visit 1), and 10 mL of test solution via HVAI (Cohorts A & B; injection visit 2). Primary endpoints were tolerability and safety outcomes. Secondary endpoints included HVAI injection duration. All 24 subjects completed visit 1; 23/24 completed visit 2. All injections were tolerated, with no serious adverse events (AEs). Following syringe pump administration, 6/24 subjects (25%) reported eight treatment-emergent AEs (TEAEs); after HVAI administration, 4/23 (17%) reported four TEAEs, all mild in severity. Mean (± SEM) injection duration via HVAI was 27.9 ± 0.8 s. Most subjects (91%, 21/23) experienced no or mild injection-site pain following HVAI administration, and 96% (22/23) said they would be willing to have the HVAI injection again. SC injection of a 10% IgG solution in combination with rHuPH20 was well tolerated at an injection rate of 10 mL/~30 s using the prototype HVAI.

Viral Nervous Necrosis due to Betanodavirus: A Case Study in Pot‐Bellied Seahorses ( Hippocampus abdominals ) - Stephen M. Pefanis; Graeme Knowles; Peter G. Mohr; Kate Swift; Jemma Bergfeld; Teresa K. Wilson; Marianne Douglas; Rachelle Hawkins; John Hoad; Adam Costin; Jacqueline Morris; David Cummins; et al. (Journal of Fish Diseases, 2025)
Betanodaviruses, members of the Nodaviridae family, are the causative agents of viral nervous necrosis in fish, resulting in great economic losses worldwide. This is the first case study describing the detection and confirmation of viral nervous necrosis in pot‐bellied seahorses ( Hippocampus abdominalis ) in Australia. Clinical signs of this infection in the seahorses included whirling, floating and cessation of feeding. Histopathological findings included prominent vacuolation in the grey matter of the brain and in the retina of the eye. Betanodavirus infection was initially detected by betanodavirus reverse transcriptase quantitative PCR and nested PCR. Sequencing confirmed the red‐spotted grouper nervous necrosis virus (RGNNV) genotype of betanodavirus. The RGNNV genotype of betanodavirus has previously been detected in Australia in fish, including barramundi ( Lates calcarifer ) and striped trumpeter ( Latris lineata ). Immunohistochemistry using antibodies directed against the capsid protein of betanodavirus demonstrated intralesional virus antigen. Betanodavirus targeted the brain, spinal cord and retina, causing intracytoplasmic vacuolation of neuronal processes and neuronal necrosis.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Quaternary rivers, tufas and mires of southern England: Description of Geological Conservation Review sites - Rebecca M. Briant; Colin A. Whiteman; B. Andrew Haggart; David R. Bridgland; Ella Egberts; Michael J. Grant; Marcus Hatch; Peter G. Knowles; Danielle C. Schreve; Philip S. Toms; Francis F. Wenban-Smith; Mark J. White (Proceedings of the Geologists' Association, 2025)

Short-term clinical and biochemical responses following treatment with dapagliflozin or ertugliflozin in horses with hyperinsulinemia: A retrospective case series - Tania Sundra; Edd Knowles; David Rendle; Erin Kelty; Guy Lester; Gabriele Rossi (Domestic Animal Endocrinology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Bark beetle impacts on forest evapotranspiration and its partitioning - John F. Knowles; Nels R. Bjarke; Andrew M. Badger; Max Berkelhammer; Joel A. Biederman; Peter D. Blanken; Mario Bretfeld; Sean P. Burns; Brent E. Ewers; John M. Frank; Jeffrey A. Hicke; Leanne Lestak; et al. (Science of The Total Environment, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Biochemical diversity of glycosphingolipid biosynthesis as a driver of Coccolithovirus competitive ecology - Jozef I. Nissimov; David Talmy; Liti Haramaty; Helen F. Fredricks; Ehud Zelzion; Ben Knowles; A. Murat Eren; Rebecca Vandzura; Christien P. Laber; Brittany M. Schieler; Christopher T. Johns; Kuldeep D. More; et al. (Environmental Microbiology, 2019)
Summary Coccolithoviruses (EhVs) are large, double‐stranded DNA‐containing viruses that infect the single‐celled, marine coccolithophore Emiliania huxleyi . Given the cosmopolitan nature and global importance of E. huxleyi as a bloom‐forming, calcifying, photoautotroph, E. huxleyi –EhV interactions play a key role in oceanic carbon biogeochemistry. Virally‐encoded glycosphingolipids (vGSLs) are virulence factors that are produced by the activity of virus‐encoded serine palmitoyltransferase (SPT). Here, we characterize the dynamics, diversity and catalytic production of vGSLs in an array of EhV strains in relation to their SPT sequence composition and explore the hypothesis that they are a determinant of infectivity and host demise. vGSL production and diversity was positively correlated with increased virulence, virus replication rate and lytic infection dynamics in laboratory experiments, but they do not explain the success of less‐virulent EhVs in natural EhV communities. The majority of EhV‐derived SPT amplicon sequences associated with infected cells in the North Atlantic derived from slower infecting, less virulent EhVs. Our lab‐, field‐ and mathematical model‐based data and simulations support ecological scenarios whereby slow‐infecting, less‐virulent EhVs successfully compete in North Atlantic populations of E. huxleyi , through either the preferential removal of fast‐infecting, virulent EhVs during active infection or by having access to a broader host range.

De novo variants in GREB1L are associated with non-syndromic inner ear malformations and deafness - Isabelle Schrauwen; Elina Kari; Jacob Mattox; Lorida Llaci; Joanna Smeeton; Marcus Naymik; David W. Raible; James A. Knowles; J. Gage Crump; Matthew J. Huentelman; Rick A. Friedman (Human Genetics, 2018)

Genetic Fingerprinting of Potato Varieties from the Northwest Potato Variety Development Program - Sapinder Bali; Vidyasagar Sathuvalli; Chuck Brown; Rich Novy; Lorie Ewing; Jeanne Debons; David Douches; Joseph Coombs; Duroy Navarre; Jonathan Whitworth; Brian Charlton; Solomon Yilma; et al. (American Journal of Potato Research, 2017)

Genetic subdivision and candidate genes under selection in North American grey wolves - Rena M. Schweizer; Bridgett M. vonHoldt; Ryan Harrigan; James C. Knowles; Marco Musiani; David Coltman; John Novembre; Robert K. Wayne (Molecular Ecology, 2016)
Previous genetic studies of the highly mobile grey wolf ( Canis lupus ) found population structure that coincides with habitat and phenotype differences. We hypothesized that these ecologically distinct populations (ecotypes) should exhibit signatures of selection in genes related to morphology, coat colour and metabolism. To test these predictions, we quantified population structure related to habitat using a genotyping array to assess variation in 42 036 single‐nucleotide polymorphisms (SNPs) in 111 North American grey wolves. Using these SNP data and individual‐level measurements of 12 environmental variables, we identified six ecotypes: West Forest, Boreal Forest, Arctic, High Arctic, British Columbia and Atlantic Forest. Next, we explored signals of selection across these wolf ecotypes through the use of three complementary methods to detect selection: F ST /haplotype homozygosity bivariate percentilae, bayescan , and environmentally correlated directional selection with bayenv . Across all methods, we found consistent signals of selection on genes related to morphology, coat coloration, metabolism, as predicted, as well as vision and hearing. In several high‐ranking candidate genes, including LEPR , TYR and SLC14A2 , we found variation in allele frequencies that follow environmental changes in temperature and precipitation, a result that is consistent with local adaptation rather than genetic drift. Our findings show that local adaptation can occur despite gene flow in a highly mobile species and can be detected through a moderately dense genomic scan. These patterns of local adaptation revealed by SNP genotyping likely reflect high fidelity to natal habitats of dispersing wolves, strong ecological divergence among habitats, and moderate levels of linkage in the wolf genome.

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Heritable changes in regional cortical thickness with age - Francois Chouinard-Decorte; D. Reese McKay; Andrew Reid; Budhachandra Khundrakpam; Lu Zhao; Sherif Karama; Pierre Rioux; Emma Sprooten; Emma Knowles; Jack W. Kent; Joanne E. Curran; Harald H. H. Göring; et al. (Brain Imaging and Behavior, 2014)

Influence of age, sex and genetic factors on the human brain - D. Reese McKay; Emma E. M. Knowles; Anderson A. M. Winkler; Emma Sprooten; Peter Kochunov; Rene L. Olvera; Joanne E. Curran; Jack W. Kent; Melanie A. Carless; Harald H. H. Göring; Thomas D. Dyer; Ravi Duggirala; et al. (Brain Imaging and Behavior, 2014)

Implications for Future Survival of Delta Smelt from Four Climate Change Scenarios for the Sacramento–San Joaquin Delta, California - Larry R. Brown; William A. Bennett; R. Wayne Wagner; Tara Morgan-King; Noah Knowles; Frederick Feyrer; David H. Schoellhamer; Mark T. Stacey; Michael Dettinger (Estuaries and Coasts, 2013)

“AmaRosa,” a Red Skinned, Red Fleshed Fingerling with High Phytonutrient Value - Charles R. Brown; Isabel Vales; Solomon Yilma; Steven James; Brian Charlton; Darrin Culp; Dan Hane; Clinton Shock; Eric Feibert; Mark Pavek; Richard Knowles; Richard Novy; et al. (American Journal of Potato Research, 2012)

Using multiple chemical indicators to characterize and determine the age of groundwater from selected vents of the Silver Springs Group, central Florida, USA - Leel Knowles; Brian G. Katz; David J. Toth (Hydrogeology Journal, 2010)

In defence of model-based inference in phylogeography - MARK A. BEAUMONT; RASMUS NIELSEN; CHRISTIAN ROBERT; JODY HEY; OSCAR GAGGIOTTI; LACEY KNOWLES; ARNAUD ESTOUP; MAHESH PANCHAL; JUKKA CORANDER; MIKE HICKERSON; SCOTT A. SISSON; NELSON FAGUNDES; et al. (Molecular Ecology, 2010)

Molecular evidence of a peripatric origin for two sympatric species of field crickets ( Gryllus rubens and G. texensis ) revealed from coalescent simulations and population genetic tests - DAVID A. GRAY; HUATENG HUANG; L. LACEY KNOWLES (Molecular Ecology, 2008)
Species pairs that differ primarily in characters involved in mating interactions and are largely sympatric raise intriguing questions about the mode of speciation. When species divergence is relatively recent, the footprint of the demographic history during speciation might be preserved and used to reconstruct the biogeography of species divergence. In this study, patterns of genetic variation were examined throughout the geographical range of two cryptic sister taxa of field crickets, Gryllus texensis and G. rubens ; mitochondrial cytochrome oxidase I ( COI ) was sequenced in 365 individuals sampled from 48 localities. Despite significant molecular divergence between the species, they were not reciprocally monophyletic. We devised several analyses to statistically explore what historical processes might have given rise to this genealogical structure. The analyses indicated that the biogeographical pattern of genetic variation does not support a model of recent gene flow between species. Instead, coalescent simulations suggested that the genealogical structure within G. texensis , namely a deep split between two geographically overlapping clades, reflects historical substructure within G. texensis . Additional tests that consider the concentration of G. rubens haplotypes in one of the two G. texensis genetic clusters suggest a model of speciation in which G. rubens was derived from one lineage of a geographically subdivided ancestor. These results indicate that, despite the contemporary sympatry of G. texensis and G. rubens, the data are indicative of an peripatric origin in which G. rubens was derived from one of the two historical partitions in the species currently recognized as G. texensis . This proposed model of species divergence suggests how the interplay of geography and selection may give rise to new species, although this requires testing with multilocus data. Specifically, the model highlights how that geographical partitioning of ancestral variation in the past may augment the selectively driven divergence of characters involved in the reproductive isolation of the species today.

Genomic analysis of Ovis aries (Ovar) MHC class IIa loci - Lynn M. Herrmann-Hoesing; Stephen N. White; Lowell S. Kappmeyer; David R. Herndon; Donald P. Knowles (Immunogenetics, 2008)

Comprehensive characterization of skeletal tissue growth anomalies of the finger coral Porites compressa - Isabelle J. Domart-Coulon; Nikki Traylor-Knowles; Esther Peters; David Elbert; Craig A. Downs; Kathy Price; Joanne Stubbs; Shawn McLaughlin; Evelyn Cox; Greta Aeby; P. Randy Brown; Gary K. Ostrander (Coral Reefs, 2006)

Gene flow on the ice: genetic differentiation among Adélie penguin colonies around Antarctica - Amy D. Roeder; Richelle K. Marshall; Amanda J. Mitchelson; Thungar Visagathilagar; Peter A. Ritchie; Donald R. Love; Trevor J. Pakai; Helen C. McPartlan; Neil D. Murray; Nick A. Robinson; Knowles R. Kerry; David M. Lambert (Molecular Ecology, 2001)
Each summer Adélie penguins breed in large disjunct colonies on ice‐free areas around the Antarctic continent. Comprising > 10 million birds, this species represents a dominant feature of the Antarctic ecosystem. The patchy distribution within a large geographical range, natal philopatry and a probable history of refugia, suggest that this species is likely to exhibit significant genetic differentiation within and among colonies. We present data from seven microsatellite DNA loci for 442 individuals from 13 locations around the Antarctic continent. With the exception of one locus, there was no significant genic or genotypic heterogeneity across populations. Pairwise F ST values were low with no value > 0.02. When all colonies were compared in a single analysis, the overall F ST value was 0.0007. Moreover, assignment tests were relatively ineffective at correctly placing individuals into their respective collection sites. These data reveal a lack of genetic differentiation between Adélie penguin colonies around the Antarctic continent, despite substantial levels of genetic variation. We consider this homogeneity in terms of the dispersal of individuals among colonies and the size of breeding groups and discuss our results in terms of the glacial history of Antarctica.

Characterizing sequence variation in the VP1 capsid proteins of foot and mouth disease virus (serotype 0) with respect to virion structure - Daniel Haydon; Susan Lea; Liz Fry; Nick Knowles; Alan R. Samuel; David Stuart; Mark E. J. Woolhouse (Journal of Molecular Evolution, 1998)

Relationships of chestnut species and New Zealand chestnut selections using morpho-nut characters - Nnadozie C. Oraguzie; David L. McNeil; David J. Klinac; Ray D. Knowles; J. Richard Sedcole (Euphytica, 1998)